The Gods of the city of Nineveh and its cultural in Assyrian impactآلهة مدينة نينوى وتأثيرها الحضاري في العهد الآشوري - Dr.Zyna Qasim (Journal of General Union of Arab Archaeologists, 2019)
Abstract The research is entitled "The Goddess of Nineveh City and its Civilizational Influence in the Assyrian Period" which is a very important topic in the field of historical and archeological studies, in the history and monuments of Nineveh in particular, and the history and archeology of Mesopotamia in general. The research deals with the most important characteristics of the religion of Mesopotamia in general and the Assyrian civilization in particular, especially the principles of vitality, analogy and continuity. The goddess Ashur (God the protector of the city of Nineveh), the god Ishtar, the god Ano, and the Nile (air god, Narkal, and any) God of wisdom. يدور البحث الموسوم " آلهة مدينة نينوى وتأثيرها الحضاري في العهد الآشوري" وهو موضوع مهم جدا فى حقل الدراسات التاريخية والاثارية على حد سواء وفى تاريخ واثار مدينة نينوى بشكل خاص وتاريخ واثار وادي الرافدين بشكل عام . البحث يتناول لأهم المميزات لديانة بلاد مابين النهرين عموما ولديانة اشور على وجه الخصوص لاسيما مبادىء الحيوية والتشبيه والاستمرارية . والالهة الاشورية المعبودة مثل ( الاله اشور( اله الحامي لمدينة نينوى ) , الاله عشتار. والاله انو, والانليل( اله الهواء , نركال, وايا( اله الحكمة. وابسو .وادد ,)